The Effect of Emotional Intelligence and Student Learning Independence on Learning Outcomes - Mislianti Mislianti; Zulfa Razi; Fona Fitry Burais; Junaidi Junaidi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
To determine the effect of emotional intelligence and learning independence on mathematics learning outcomes. This study uses a quantitative approach, with a correlational design of ex-post facto research type. Sampling in this study was done by purposive sampling. Data collection techniques in this study were questionnaires and documentation of learning outcomes. The questionnaire used in this study was divided into two, namely the emotional intelligence questionnaire and the learning independence questionnaire. Even semester exam results will be used as data on mathematics learning outcomes. The data analysis technique used the F-test. The results of the research data analysis showed that emotional intelligence had an effect on student learning outcomes by 12.2%. Independent learning of students also affects the learning outcomes of mathematics by 10.5%. This shows that emotional intelligence and learning independence have a low relationship with learning outcomes